Transforming Small-Scale Garment Production: Lean Manufacturing and VSM Strategies for Enhanced Productivity in Makassar's MSMEs - Asrul Fole; Khoerun Nisa Safitri (Journal of Industrial System Engineering and Management, 2025)
This research aims to examine the application of Lean Manufacturing and Value Stream Mapping (VSM) in enhancing productivity within micro, small, and medium enterprises (MSMEs) in the garment sector in Makassar. By focusing on identifying and reducing waste, this study analyzes cycle times and activity mapping to uncover bottlenecks that hinder operational efficiency. The analysis results indicate that the implementation of Lean principles can lead to significant improvements in production processes, including reductions in cycle time and waiting time. Furthermore, this research highlights the importance of eliminating non-value-added activities and integrating advanced technologies, such as automation and real-time tracking systems, to further enhance efficiency. These findings not only provide valuable insights for industry practitioners but also offer practical guidance for optimizing production processes. By adopting Lean strategies, garment MSMEs in Makassar can improve their competitiveness in an increasingly competitive market while contributing to regional economic development. This study is expected to serve as a reference for researchers, practitioners, and policymakers in efforts to create a more efficient and sustainable garment industry in Indonesia.